A chromatin accessibility landscape during early adipogenesis of human adipose-derived stem cells. (31st December 2022) - Li, Sen; Zong, Xiaolin; Zhang, Liheng; Li, Luya; Wu, Jianxin
ABSTRACT: Obesity has become a serious global public health problem; a deeper understanding of systemic change of chromatin accessibility during human adipogenesis contributes to conquering obesity and its related diseases. Here, we applied the ATAC-seq method to depict a high-quality genome‐wide time-resolved accessible chromatin atlas during adipogenesis of human adipose-derived stem cells (hASCs). Our data indicated that the chromatin accessibility drastic dynamically reformed during the adipogenesis of hASCs and 8 h may be the critical transition node of adipogenesis chromatin states from commitment phase to determination phase. Moreover, upon adipogenesis, we also found that the chromatin accessibility of regions related to anti-apoptotic, angiogenic and immunoregulatory gradually increased, which is beneficial to maintaining the health of adipose tissue (AT). Finally, the chromatin accessibility changed significantly in intronic regions of peroxisome proliferator‐activated receptor γ during adipogenesis, and these regions were rich in transcription factors binding motifs that were exposed for further regulation. Overall, we systematically analysed the complex change of chromatin accessibility occurring in the early stage of adipogenesis and deepened our understanding of human adipogenesis. Furthermore, we also provided a good reference data resource of genome‐wide chromatin accessibility for future studies on human adipogenesis.